2020
DOI: 10.1021/jacs.0c08174
|View full text |Cite
|
Sign up to set email alerts
|

Shape-Shifting Peptide Nanomaterials: Surface Asymmetry Enables pH-Dependent Formation and Interconversion of Collagen Tubes and Sheets

Abstract: The fabrication of dynamic, transformable biomaterials that respond to environmental cues represents a significant step forward in the development of synthetic materials that rival their highly functional, natural counterparts. Here, we describe the design and synthesis of crystalline supramolecular architectures from charge-complementary heteromeric pairs of collagen-mimetic peptides (CMPs). Under appropriate conditions, CMP pairs spontaneously assemble into either 1D ultraporous (pore diameter > 100 nm) tube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 76 publications
0
41
0
Order By: Relevance
“…The sheet form was dominant at neutral pH, which suggested that the tubes represented a kinetic product. A similar pH-dependent transition between sheets and scrolled tubes was reported for a series of designed collagen-mimetic peptides (Merg et al ., 2020). These data suggested that preformed supercoiled peptide motifs could serve as protomers for the creation of shape-shifting nanomaterials that could toggle between sheet-like and tubular forms.…”
Section: Coiled-coil Filamentsmentioning
confidence: 99%
“…The sheet form was dominant at neutral pH, which suggested that the tubes represented a kinetic product. A similar pH-dependent transition between sheets and scrolled tubes was reported for a series of designed collagen-mimetic peptides (Merg et al ., 2020). These data suggested that preformed supercoiled peptide motifs could serve as protomers for the creation of shape-shifting nanomaterials that could toggle between sheet-like and tubular forms.…”
Section: Coiled-coil Filamentsmentioning
confidence: 99%
“…Rigid diblock monomers can also incorporate ionic domains to control directional growth, which allows the ordered assembly of 2D bilayers from flat amphiphilic peptoids 75 and cylindrical coiled-coils. 57 Our group recently reported cyclic d / l -alternating peptides that grow 1D nanotubes via backbone H-bonding, 76 whose hydrophobic face induces their subsequent assembly into 2D bilayers by inter-tubular hydrophobic interactions ( Fig. 2C ).…”
Section: Directing Monomer Self-assembly In 2dmentioning
confidence: 98%
“…56 In certain cases, implementation of comonomers with geometrical restrictions can be used to control the structural fate of the nal assemblies. 57 Frustration of the crystallisation process can also be achieved by monomer composition to obtain complex structures such as toroidal micelles with a tuneable size. 58 Stoppers.…”
Section: Structural Controlmentioning
confidence: 99%
“…These researchers further engineered the intrinsically disordered proteins (IDPs) based on the sequence-property relationship, thus enabling the modulation of phase separation in living cells [80]. Conticello and co-workers [81] created pH-dependent interconversion of collagen tubes and sheets using heteromeric pairs of collagen-mimetic peptides with carefully selected number and position of charged residues for charge complementary. The controllable transformation between different assembly structures and morphologies would be promising in designing versatile and smart carriers of a diverse spectrum of molecular payloads.…”
Section: Genetically Engineered Protein Assembliesmentioning
confidence: 99%